Determinants of Financial Performance in Energy Sector State-Owned Enterprises: Evidence from PT. PLN (Persero) - Wahyu Nugroho (CV. Era Digital Nusantara, 2026)
This study aims to determine and examine the simultaneous and partial effects of operating costs (measured by BOPO) and liquidity (measured by Current Ratio) on the financial performance (measured by Return on Assets/ROA) of PT. PLN (Persero). The research population and sample consist of the quarterly financial report data of PT. PLN (Persero) from 2017 (Q3) to 2024 (Q4), comprising 30 quarterly observations selected through a saturated sampling method. Data were obtained from official financial publications and analyzed using multiple linear regression. The empirical results indicate that operating costs (BOPO) have a negative and significant effect on financial performance, while liquidity (Current Ratio) has a positive and significant effect on financial performance. Simultaneously, operating costs and liquidity exert a significant influence on financial performance, as evidenced by an F-statistic value of 119.86 (p < 0.05) and a high R-Square of 0.899. These findings imply that the financial performance of PT. PLN (Persero) is highly sensitive to operational efficiency and short-term asset management, suggesting that corporate strategies must prioritize suppressing the BOPO ratio and maintaining an optimal current ratio to ensure sustainable profit growth.